UNDERSTANDING TEACHER TALK TO SUPPORT STUDENTS’ COMMUNICATIVE COMPETENCE - Hermanto Hermanto (JURNAL SOSIAL HUMANIORA (JSH), 2015)
Most people learn a foreign language in classrooms. Classroom language is the chief source of foreign language learning and in some places it is the only source. It functions not only as a major source of language learning but also as a tool by which a foreign language is taught. Based on the theory of second language acquisition (SLA), it is believed that the language that teachers address to L2 learners will to some degree influence language learning. Since a better understanding of the use of teachers’ language can undoubtedly help students improve their learning, students can make a better use of teacher talk to learn the target language.